Stress control and dislocation reduction in the initial growth of GaN on Si (111) substrates by using a thin GaN transition layer. Issue 32 (19th July 2019) - Wang, Kun; Li, Mengda; Yang, Zhijian; Wu, Jiejun; Yu, Tongjun
Abstract : A thin GaN transition layer technology is proposed to control stress and reduce the dislocation density in the initial GaN growth. Abstract : A thin GaN transition layer (GTL) technology is proposed to control stress and reduce the dislocation density in the initial growth of GaN on an AlN nucleation layer on Si (111) substrates. The GTL has a thickness of 50 nm and is the thinnest transition layer reported for GaN growth on Si substrates. It is found that the density and aspect ratio of GaN islands markedly decrease and the size of GaN islands observably increases under GTL growth conditions. Therefore, the compressive stress relaxation in the initial GaN growth caused by island deformation and island coalescence can be significantly reduced and more compressive stress is built up in the GaN epilayer. Meanwhile, the dislocations originating from the AlN nucleation layer are inclined at an average angle as large as 37° and therefore, most of the dislocations interact and annihilate in the GTL. In this way, efficient stress control and dislocation reduction in the initial GaN growth are simultaneously realized. Moreover, thanks to great reduction of the dislocation density in the GTL, the compressive stress relaxation due to dislocation inclination in subsequent GaN growth is also significantly decreased. As a result, a 1.5 μm crack-free GaN epilayer, whose full width at half maximum (FWHM) values of the (002) and (102) X-ray rocking curves are 270 and 521 arcsec, respectively, is obtained. With a simple growth process, the quality of the GaN epilayer directly grown on the AlN nucleation layer is greatly improved, which demonstrates great application potential for the growth of a fully vertical device structure on Si substrates.